University social responsibility – theory vs. practice - Buchta, Krystyna; Jakubiak, Monika; Skiert, Małgorzata; Wilczewski, Adam (Research Papers of Wrocław University of Economics, 2018)
The subject matter of the present paper pertains to issues associated with thesignificance of university social responsibility. The paper outlines theoretical conceptsand results of own studies connected with activities undertaken by a socially responsibleuniversity. Actions which take stakeholders’ expectations into consideration are regarded asresponsible. Consequently, vocational training of university graduates constitutes the focus ofthe paper. Results of own studies indicated several discrepancies between the expected andacquired competences of university graduates
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 22-33
Keywords: university; university’s social responsibility; graduates; employers; szkoła wyższa; społeczna odpowiedzialność uczelni; absolwenci; pracodawcy